Cavitation-corrosion behaviors of HVOF sprayed WC-25WB-10Co-5NiCr and MoB-25NiCr coatings. Issue 13 (September 2020) - Du, Jin; Zhang, Jianfeng; Xu, Jinyong; Zhang, Chao
Abstract: Cavitation erosion, corrosion and synergism behaviors of HVOF sprayed WC-25WB-10Co-5NiCr and MoB-25NiCr coatings were investigated in this study. Conventional WC-10Co-4Cr and Cr3 C2 -25NiCr coatings were also characterized for comparison purposes. The cavitation erosion and cavitation-corrosion experiments were carried out in deionized water and 3.5 wt% NaCl solution respectively. The average mass loss rate was defined to assess the destruction of the coating surface. The cavitation erosion resistance and the cavitation-corrosion resistance were adopted to quantitatively analyze the difference of cavitation erosion and cavitation-corrosion performance of the coatings. The potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) tests were employed to evaluate the corrosion resistance of all the coatings. In addition, the equivalent circuit models were designed to fit the EIS. The cumulative mass loss of all the coatings was measured under the conditions of pure cavitation erosion, pure corrosion and cavitation-corrosion. The total mass loss rate, pure cavitation rate, pure corrosion rate as well as synergistic mass loss rate were calculated to discuss their relative contributions responsible for the material removal. The cavitation-corrosion mechanisms were also discussed by analyzing the eroded surface for all the coatings.